PENENTUAN SENYAWA BIOAKTIF EKSTRAK DAGING SIPUT BAKAU (Terebralia sulcata) DENGAN KROMATOGRAFI LAPIS TIPIS (KLT) - Sumarto Sumarto; Desmelati Desmelati; Dahlia Dahlia; Bustari Hasan; M Azwar (Berkala Perikanan Terubuk, 2011)
This research was conducted for aims to determine the class of activecompounds contained in the mangrove snail meat that was extracted using hexaneand methanol solvents. Active compound was determined using maceration, thinlayer chromatography (TLC) and phytochemical test methods. At plate TLC haveRf 0,86 cm and 0,62 cm and active compounds derived from the mangrove snail(Terebralia sulcata) are flavonoids (polar and non polar) and non polar saponinand alkaloid .